Does Perceived Behavioral Control Mediate the Effect of Entrepreneurial Knowledge on Student Entrepreneurship Intentions in Indonesia? - Simatupang, Taruli Serefina; Machmud, Amir; Suwatno, (International Journal of Psychosocial Rehabilitation, 2020)
This research is motivated by the low intentions of entrepreneurship in high school students in Indonesia. This study aims to analyze the mediating effect of perceived behavioral control on the effect of entrepreneurial knowledge on entrepreneurial intentions. This study uses an explanatory survey method with a quantitative approach. Data collection was done through a questionnaire, the population in research of Christian high school students in Bandung City, West Java, Indonesia amounting to 512. To use a sampling technique of 299 people. The collected data was then analyzed using Multiple Regression Analysis (MRA) using Macro Process Software from Hayes. The results of this study indicate that perceived behavioral control mediates the effect of entrepreneurial knowledge on the entrepreneurial intentions of high school students in Indonesia. These findings indicate that to increase entrepreneurial intentions, the learning process in high school needs to be emphasized in efforts to increase perceived behavioral control